Plasma proteome analysis of cervical intraepithelial neoplasia and cervical squamous cell carcinoma. - Looi, M.L.; Karsani, S.A.; Rahman, M.A.; Dali, A.Z.H.M.; Ali, S.A.M.; Ngah, W.Z.W.; Yusof, Y.A.M. (Indian Academy of Sciences, 2009)
Although cervical cancer is preventable with early detection, it remains the second most common malignancy among women. An understanding of how proteins change in their expression during a particular diseased state such as cervical cancer will contribute to an understanding of how the disease develops and progresses. Potentially, it may also lead to the ability to predict the occurrence of the disease. With this in mind, we aimed to identify differentially expressed proteins in the plasma of cervical cancer patients. Plasma from control, cervical intraepithelial neoplasia (CIN) grade 3 and squamous cell carcinoma (SCC) stage IV subjects was resolved by two-dimensional gel electrophoresis and the resulting proteome profiles compared. Differentially expressed protein spots were then identified by mass spectrometry. Eighteen proteins were found to be differentially expressed in the plasma of CIN 3 and SCC stage IV samples when compared with that of controls. Competitive ELISA further validated the expression of cytokeratin 19 and tetranectin. Functional analyses of these differentially expressed proteins will provide further insight into their potential role(s) in cervical cancer-specific monitoring and therapeutics.